Associations of the melanocortin 3 receptor C17A + G241A haplotype with body composition and inflammation in African‐American adults. (2nd April 2019) - Demidowich, Andrew P.; Parikh, Viraj J.; Dedhia, Nicket; Branham, Rachel E.; Madi, Samar A.; Marwitz, Shannon E.; Roberson, Robin B.; Uhlman, Andrew J.; Levi, Noah J.; Mi, Sarah J.; Jun, Joo Yun; Broadney, Miranda M.; et al.
Abstract: Background: The MC3R haplotype C17A + G241A, which encodes a partially inactivated receptor, has high prevalence in individuals of predominately African ancestry. In pediatric cohorts, homozygosity for this common variant has been associated with obesity, reduced lean mass, and greater fasting insulin. However, metabolic and body composition measures have not been well studied in adults with this haplotype. Methods: A convenience sample of 237 healthy African‐American adult volunteers was studied. TaqMan assays were used to genotype MC3R variants. Labs were drawn in the morning in the fasted state. Body composition data was obtained via dual‐energy X‐ray absorptiometry. An analysis of covariance was used to examine the associations of genotype with metabolic and body composition measures controlling for age and sex. Results: Individuals homozygous for the MC3R C17A + G241A haplotype had significantly greater body mass index, fat mass, fat mass percentage, and C‐reactive protein, with reduced lean mass percentage as compared to heterozygous and wild‐type participants (all p s < 0.05); fasting insulin was marginally nonsignificant between groups ( p  = 0.053). After adjusting for fat mass, laboratory differences no longer remained significant. Conclusions: Homozygosity for MC3R C17A + G241A is associated with increased adiposity in African‐American adults. Further studies are needed to elucidate the mechanisms behind these associations.